Measuring the Resilience of Energy Distribution Systems - Willis, Henry H. (RAND Corporation, 2015)
Energy distribution systems are vulnerable to diverse and dynamic disruptions, so the U.S. Department of Energy is developing a strategy to improve the resilience of these systems. In support of this effort, researchers develop a framework for measuring the resilience of energy systems and summarize the state of metrics for resilience of the electric power, refined oil, and natural gas distribution systems.